Environmental communication and disaster mitigation by mobile application and website - Meidina, Aulia Putri; Murfi, Alrafki (Jurnal Kajian Komunikasi, 2024)
Background: Indonesia is a disaster-prone area, situated in the equatorial zone where several tectonic plates converge, and the Ring of Fire runs through. Indonesia requires an effective disaster mitigation system to minimize risks and losses during disasters. Meteorological, Climatological, and Geophysical Agency (BMKG) is a non-departmental government institution. Through its mobile application and official website, BMKG actively provides various information accessible to all Indonesians. Purpose: The research aimed to understand how BMKG conducts environmental communication and disaster mitigation through a mobile application and website. Methods: This research is descriptive qualitative using a constructive paradigm. The data was collected using documentation and observation studies. The authors carried out content analysis using Philipp Mayring’s methods on the “Info BMKG” application and the website http://www.bmkg.go.id/. Results: The BMKG application and website cover some aspects of environmental communication, including rhetoric, media, public participation, and education campaigns, delivering a range of environmental messages. They facilitate disaster mitigation by providing information and vulnerability maps for different types of disasters but lack details on regulatory measures and planning for disaster-prone areas. Conclusion: The BMKG application and website effectively communicate environmental and disaster-related information but need to improve coverage, speed of notifications, and include more details on regulation and planning for disaster-prone areas. Implications: This study suggests the need to enhance the platforms’ content and user education. Besides, it emphasizes theoretical implications for communication, public participation, and media theories in the context of disaster risk reduction.